The forming of pupils musical styles in the condition of extra-curricular work - V.M. Sergeeva (Academy of Cognitive and Natural Sciences, 2006)
In article the theoretical and the practical aspects of the problem of the forming of pupils musical styles tn the condition of extra-curricular work are considered. Modern methods of their development and positive influence on the common culture of the growing generation are defined.